Aggregate Economic Growth with Subsistence Consumption - Thomas Steger (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1998)
Four stylised facts of economic growth in DCs are set up initially. Despite its obvious simplicity the linear growth model with subsistence consumption is able to reproduce two of them: a rise in the saving rate along with per capita income as well as ß-divergence. The speed of convergence shows extraordinarily low values at early stages of economic development. Hence, the big diversity in growth rates can partly be explained to represent transitional phenomena. However, if international symmetry with respect to preferences and technology is supposed, the possible range of different growth rates is restricted. An extension of the basic model allows a more satisfactory explanation of the big diversity in growth experiences and additionally reproduces the hump-shaped relation between the growth rate and the level of per capita income.
Keywords: 330